Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

Synthesis and antifungal activity of 1,5-disubstituted-1,2,3-triazole containing fluconazole analogues - Pore, Vandana S.; Jagtap, Manisha A.; Agalave, Sandip G.; Pandey, Atindra K.; Siddiqi, Mohammad I.; Kumar, Vikash; Shukla, Praveen K. (Medchemcomm, 2012)
Fluconazole based novel mimics containing 1,5-disubstituted 1,2,3-triazoles were synthesized by using Ru catalysed 1,3 dipolar cycloaddition. All the newly synthesized compounds and pure enantiomers were more potent than fluconazole against Candida albicans. Docking of 9A and 9B showed different conformation in the active site of Cyp51 of Candida albicans. The more active compounds 2 and 2A did not exhibit any toxicity up to 3.12 mu g mL(-1) against mammalian cell line L929.

Synthesis of substituted 2,6-dicyanoanilines and related compounds. a review - Borate, Hanumant B.; Kudale, Ananada S.; Agalave, Sandip G. (Organic Preparations and Procedures International, 2012)

Alumina-supported copper iodide: an efficient and recyclable catalyst for microwave-assisted synthesis of 1,4-disubstituted 1,2,3-triazoles via three-component reaction in water - Agalave, Sandip G.; Pharande, Shrikant G.; Gade, Swapna M.; Pore, Vandana S. (Asian Journal of Organic Chemistry, 2015)
A one-pot procedure for the synthesis of 1,4-disubstituted 1,2,3-triazoles by a three-component reaction of allyl or benzyl halides, sodium azide, and terminal alkynes over a neutral alumina-supported copper iodide catalyst has been developed. The products were isolated by simple filtration followed by washing of the catalyst with acetone. The products were obtained in almost pure form in up to 98% yield (TON 495). The catalyst can be recycled for more than eight subsequent reactions. The halides are directly converted into triazoles via in situ formation of azides and thus handling of hazardous azides can be avoided. The broad scope of this protocol is shown by the synthesis of a variety of diversely substituted 1,2,3-triazoles and also two-component azide-alkyne click reaction. The key features of this procedure are the use of water as a solvent, recyclability of the catalyst up to eight runs without appreciable loss of activity, and high yields of products. The catalyst has been fully characterized by FTIR, solid-state NMR and EDX spectroscopy, ESEM, TGA, and XRD.
Keywords: 1; 2; 3-triazoles; 4; copper(I) iodide; Cycloaddition; disubstituted 1; Microwave chemistry; supported catalysts

Bile acid hydrazides: gelation, structural, physical and spectroscopic properties - Pore, Vandana S.; Agalave, Sandip G.; Pharande, Shrikant G.; Patil, Prashant A.; Kotmale, Amol S. (New Journal of Chemistry, 2015)
Synthesis and gelation properties of a series of novel bile acid hydrazides are presented. These compounds are found to undergo self-assembly leading to organogelation in certain organic solvents. Compound 1 was found to be the most ``effective'' gelator in this series. The properties of this gel have been thoroughly investigated by conventional methods typical for molecular gel studies. Sol gel transition temperature (T-g) of chloroform gels of compounds 1 and 3 was found to increase with increase in the chain length. Sol-gel transition was probed using the isothermal time test and results show that there is instantaneous increase in both the moduli after shear melting, which suggests that the kinetics of formation of the network was very fast. IR and NMR studies revealed hydrogen bonding between amidic carbonyl in the side chain and hydroxyl groups of cholic acid.

Design and synthesis of new fluconazole analogues - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I. (Organic & Biomolecular Chemistry, 2015)
We have synthesized new fluconazole analogues containing two different 1,2,3-triazole units in the side chain. The synthesis of new amide analogues using a variety of acids is also described. All the compounds showed very good antifungal activity. A hemolysis study of the most active compounds 6e and 13j showed that both compounds did not cause any hemolysis at the dilutions tested. These compounds did not exhibit any toxicity to L929 cells at MIC and lower concentrations. In the docking study, the overall binding mode of 6e and 13j appeared to be reasonable and provided a good insight into the structural basis of inhibition of Candida albicans Cyp51 by these compounds.

MnO2@Fe3O4 Magnetic Nanoparticles as Efficient and Recyclable Heterogeneous Catalyst for Benzylic sp(3) C-H Oxidation - Pandey, Akanksha M.; Agalave, Sandip G.; Vinod, Chathakudath P.; Gnanaprakasam, Boopathy (Chemistry-An Asian Journal, 2019)
Herein, we report a highly chemoselective and efficient heterogeneous MnO2@Fe3O4 MNP catalyst for the oxidation of benzylic sp(3) C-H group of ethers using TBHP as a green oxidant to afford ester derivatives in high yield under batch/continuous flow module. This catalyst was also effective for the benzylic sp(3) C-H group of methylene derivatives to furnish the ketone in high yield which can be easily integrated into continuous flow condition for scale up. The catalyst is fully characterized by spectroscopic techniques and it was found that 0.424 % MnO2@Fe3O4 catalyzes the reaction; the magnetic nanoparticles of this catalyst could be easily recovered from the reaction mixture. The recovered catalyst was recycled for twelve cycles without any loss of the catalytic activity. The advantages of MnO2@Fe3O4 MNP are its catalytic activity, easy preparation, recovery, and recyclability, gram scale synthesis with a TOF of up to 14.93 h(-1) and low metal leaching during the reaction.